Saving Private Ryan - Spielberg, Steven, 1947-; Bryce, Ian.; Gordon, Mark, 1956-; Levinsohn, Gary.; Rodat, Robert; Hanks, Tom.; Burns, Edward, 1968-; Damon, Matt.; Sizemore, Tom, 1961-; DreamWorks Pictures; Paramount Pictures Corporation; Amblin Entertainment (Firm); et al. (Universal City, CA : DreamWorks Home Entertainment, 1999)
Captain John Miller must take his men behind enemy lines to find Private Ryan, whose three brothers have been killed in combat. Faced with impossible odds, the men question their orders. Why are eight men risking their lives to save just one? Surrounded by the brutal realities of war, each man searches for his own answer and the strength to triumph over uncertain future with honor, decency and courage.
Anamorphic widescreen: 1.85:1.
Special features include: interactive menu, message from the director, two theatrical trailers, production notes, cast and filmmakers' bios.
Originally released as a motion picture in 1998.
Director of photography, Janusz Kaminski ; editor, Michael Kahn ; music, John Williams.
Tom Hanks, Edward Burns, Matt Damon, Tom Sizemore.
MPAA rating: R.
Keywords: 1939 - 1945; Feature films; War films; World War, 1939-1945 -- Campaigns -- France -- Normandy -- Drama; Feature films; Military campaigns; War films; France -- Normandy; Drama